Pengaruh Pengeluaran Pemerintah dalam Bidang Pendidikan dan Kesehatan, Tingkat Kemiskinan, dan Pendapatan Perkapita Terhadap Indeks Pembangunan Manusia di Kota Banjarmasin - Rahimah Rahimah; Ika Chandriyanti (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
This study aims to determine the effect of variables governtment spending on education and health, poverty levels, and income per capita on the Human Development Index in Banjarmasin. The data used in this study is secondary time series data for the period 2010 – 2019. The research method used is a quantitative method. The data collection technique in this research is through literature study. The data analysis technique used multiple linear regression analysis method. The results showed that the variables of government spending on education and health, poverty levels, and income per capita simultaneously had a significant effect on the human development index. Partially shows that the variables of government spending on education and income per capita are positive and have a significant effect on the human development index. Meanwhile, the variables of government spending on health sector and poverty levels partially have no significant effect and are negatively related to the human development index.